Highly durable iridium-nitrogen doped platinum-cobalt-carbon catalysts, methods of making and applications thereof
Patent Information
- Application Number
- CN202511384720.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-26
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2045-09-26
AI Technical Summary
[0002]现有铂钴碳(PtCo/C)合金催化剂虽可通过合金化减少贵金属用量并提高氧还原(ORR)活性,但在高电位、酸性、高湿、高氧自由基环境中长期运行时,易发生钴溶出、颗粒长大及碳载体腐蚀,导致活性与耐久性急剧下降
(1)本发明微量铱以特定的形式分散并与氮源形成Ir-N结构,为铂钴合金提供高密度、高结合能的锚定位点,显著抑制高温热处理或长期运行过程中的颗粒迁移与团聚。
Smart Images

Figure CN121215787B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalyst preparation technology, specifically relating to a highly durable iridium-nitrogen-doped platinum-cobalt-carbon catalyst, its preparation method, and its application. Background Technology
[0002] While existing platinum-cobalt-carbon (PtCo / C) alloy catalysts can reduce the amount of precious metals and improve oxygen reduction (ORR) activity through alloying, they are prone to cobalt dissolution, particle growth, and carbon support corrosion during long-term operation in high-potential, acidic, high-humidity, and high-oxygen free radical environments, leading to a sharp decline in activity and durability. Summary of the Invention
[0003] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a highly durable iridium-nitrogen-doped platinum-cobalt-carbon catalyst, its preparation method, and its applications. This invention introduces trace amounts of Ir into the PtCo lattice in a specific form, and in synergy with nitrogen doping, forms a stronger metal-NC bonding network, significantly inhibiting cobalt dissolution and particle growth. This significantly improves the durability of the platinum-cobalt-carbon catalyst in full cells, resulting in a catalyst that combines high activity with ultra-long durability.
[0004] To achieve the above technical objectives, the technical solution adopted in the embodiments of the present invention is as follows: In a first aspect, embodiments of the present invention provide a method for preparing a highly durable iridium-nitrogen-doped platinum-cobalt-carbon catalyst, comprising the following steps: (1) Disperse the platinum source, cobalt nitrate hexahydrate and carbon support in water, and fully disperse them at room temperature to form a uniform slurry. Heat the slurry to 40-50℃, add an appropriate amount of the first nitrogen source, stir thoroughly, adjust the pH of the slurry to 9.5-10.5, and stir for 1-24 hours to form a platinum-cobalt-nitrogen-carbon precursor slurry. (2) Add iridium source, cobalt nitrate hexahydrate, second nitrogen source and carbon support to an appropriate amount of water and disperse them into a slurry. Add the slurry to the platinum cobalt nitrogen carbon precursor slurry in step (1), heat to 60-80℃ and react for 4-48h. Collect the slurry after reaction and precipitate. Wash the precipitate repeatedly with deionized water and vacuum dry at 60-80℃ for 4-12h to obtain iridium nitrogen doped platinum cobalt carbon precursor. (3) The iridium nitrogen-doped platinum cobalt carbon precursor obtained in step (2) is heated to 200-250°C at a heating rate of 5-10°C / min under a calcination atmosphere and held for 20-40 min. Then, the temperature is increased to 600-700°C and held for 2-8 h. Finally, the temperature is increased to 800-950°C and held for 1-2 h. The mixture is then naturally cooled to room temperature to obtain a black powder. (4) The black powder obtained in step (3) is placed in an acidic solution and stirred at 30-50°C for 2-48 hours to remove surface impurities. It is then washed with deionized water until neutral and dried under vacuum at 60-80°C to finally obtain an iridium nitrogen-doped platinum cobalt carbon catalyst.
[0005] Further, in step (1), the platinum source is one of chloroplatinic acid hexahydrate and platinum sulfate tetrahydrate; the first nitrogen source is one or more of melamine, ethylenediamine and p-phenylenediamine; In steps (1) and (2), the carbon support is one or more of mesoporous carbon support, porous carbon and acetylene black.
[0006] Further, in step (1), the platinum source is chloroplatinic acid hexahydrate, the carbon support is a mesoporous carbon support, and the first nitrogen source is p-phenylenediamine or ethylenediamine.
[0007] Furthermore, in step (2), the iridium source is one or more of hexachloroiridate hydrate, ammonium hexachloroiridate, and iridium trichloride trihydrate.
[0008] Furthermore, in step (2), the second nitrogen source is one or more of dimethylimidazole, o-phenanthroline and glutamine.
[0009] Furthermore, in step (3), the roasting atmosphere is one or more of nitrogen, argon and hydrogen.
[0010] Further, in step (4), the acidic solution is one or a mixture of several of hydrochloric acid, sulfuric acid, acetic acid and citric acid, with a concentration of 0.5-1 mol / L.
[0011] Further, in step (4), the iridium-nitrogen-doped platinum-cobalt-carbon catalyst contains 0.5-1.5% iridium, 0.5-2% nitrogen, 40-50% platinum, 3-5% cobalt, and the remainder is carbon.
[0012] Secondly, embodiments of the present invention provide a high-durability iridium-nitrogen-doped platinum-cobalt-carbon catalyst, which is prepared using the preparation method described in the first aspect.
[0013] Thirdly, embodiments of the present invention provide the application of the high-durability iridium-nitrogen-doped platinum-cobalt-carbon catalyst described in the second aspect, wherein the catalyst is used in a fuel cell for the fuel cell cathode.
[0014] The beneficial effects of the technical solution provided by the embodiments of the present invention are as follows: (1) The trace amount of iridium in this invention is dispersed in a specific form and forms an Ir-N structure with a nitrogen source, providing high-density, high-binding-energy anchoring points for platinum-cobalt alloys, which significantly inhibits particle migration and agglomeration during high-temperature heat treatment or long-term operation.
[0015] (2) In this invention, iridium and nitrogen synergistically regulate the electronic structure of the platinum-cobalt alloy surface, reduce the tendency of Co oxidation and dissolution, and suppress structural deformation. The life of the membrane electrode is greatly extended by doping with trace amounts of iridium and nitrogen.
[0016] (3) In this invention, the N in nitrogen-doped carbon provides electrons to Ir and Pt, which induces the d-band center to shift downward, optimizes the *OH desorption energy barrier, and thus enhances the intrinsic oxygen reduction activity.
[0017] (4) In this invention, nitrogen atoms enter the sp² carbon skeleton, increase the degree of graphitization and form a strong C–N covalent network, reduce the carbon oxidation rate at high potential, and thus reduce corrosion and peeling during the durability process.
[0018] (5) The trace amount of iridium in this invention isolates the platinum surface and inhibits Oswald ripening, so that the mass activity (MA) of the catalyst remains above 97% after 50,000 ultra-long square wave cycles at 0.6–0.95V.
[0019] (6) The preparation method of the present invention adopts the conventional wet chemical-heat treatment-acid washing route, without the need for special processes or expensive equipment, and can be directly scaled up to the kilogram-level batch preparation at low cost.
[0020] (7) The preparation method of the present invention is not only applicable to platinum-cobalt catalysts, but also to the doping of other catalysts, and has good applicability. Attached Figure Description
[0021] Figure 1 This is a high-resolution transmission electron microscope image of the iridium nitrogen-doped platinum cobalt carbon catalyst prepared in Example 2 of this invention.
[0022] Figure 2 These are the X-ray powder diffraction patterns of the undoped platinum-cobalt-carbon catalyst of Comparative Example 1 and the iridium-nitrogen-doped platinum-cobalt-carbon catalyst prepared in Example 3 of this invention.
[0023] Figure 3 This is a comparison of linear voltammetric scan curves of the particle durability test after 50,000 square wave cycles in the three-electrode system of the catalyst prepared in Example 3 of this invention.
[0024] Figure 4 This is a comparison of the polarization curves of a single fuel cell made using the iridium-nitrogen-doped platinum-cobalt-carbon catalyst prepared according to the method of Example 3 of this invention before and after a 50,000-cycle square wave test.
[0025] Figure 5 This is a comparison of the polarization curves of a single fuel cell prepared using the method of Comparative Example 1 of this invention before and after a 50,000-cycle square wave test.
[0026] Figure 4and Figure 5 The test conditions were as follows: hydrogen / air pressure: 1.6 / 1.5 bar, hydrogen / air metering ratio: 1.5 / 2.0, hydrogen / air inlet temperature: 80℃ / 80℃, hydrogen / air dew point temperature: 64℃ / 64℃, cooling chamber inlet temperature: 80℃, and battery area: 25 cm². 2 .
[0027] Figure labeling: 1-Iridium nitrogen-doped platinum-cobalt alloy nanoparticles; 2-Carbon support. Detailed Implementation
[0028] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0029] Example 1 A method for preparing a highly durable iridium-nitrogen-doped platinum-cobalt-carbon catalyst includes the following steps: (1) Disperse 1.2g chloroplatinic acid hexahydrate, 0.4g cobalt nitrate hexahydrate and 0.5g carbon support (BP2000 porous carbon) in 100g water, and disperse them thoroughly at room temperature to form a uniform slurry. Heat the mixture to 40℃, add 0.5g ethylenediamine, stir thoroughly for 5min, add sodium hydroxide solution with a concentration of 0.1mol / L to adjust the pH of the slurry to 9.5, and stir for 1h to form a platinum cobalt nitrogen carbon precursor slurry; (2) Add 0.0134g of hexachloroiridium acid hydrate, 0.2g of cobalt nitrate hexahydrate, 0.2g of dimethylimidazole and 0.1g of carbon support (BP2000 porous carbon) to 50g of water and disperse them into a slurry. Add the slurry to the platinum cobalt nitrogen carbon precursor slurry in step (1), heat to 60℃ and react for 4h. Collect the precipitate after reaction, wash the precipitate repeatedly with deionized water, and vacuum dry at 60℃ for 12h to obtain iridium nitrogen doped platinum cobalt carbon precursor. (3) The iridium nitrogen-doped platinum cobalt carbon precursor obtained in step (2) was heated to 200°C for 30 min in an H2-Ar atmosphere with a flow rate of 200 mL / min (H2 volume fraction of 5%), and then heated to 700°C for 2 h, and then heated to 800°C for 1 h. The precursor was then naturally cooled to room temperature to obtain a black powder. (4) The black powder obtained in step (3) was placed in a hydrochloric acid solution with a concentration of 0.5 mol / L, stirred at 50°C for 2 h to remove surface impurities, washed with deionized water until neutral, and vacuum dried at 80°C for 4 h to finally obtain the iridium nitrogen-doped platinum cobalt carbon catalyst.
[0030] Electrochemical performance testing conditions: Three-electrode system, with the working electrode having a geometric area of 0.19625 cm². 2 A rotating disk electrode (RDE) was used. The catalyst to be tested was uniformly loaded on the working electrode. A 10 mm × 5 mm platinum mesh was used as the counter electrode, and a reversible hydrogen electrode was used as the reference electrode. The electrolyte was 0.1 mol / L HClO4 saturated with oxygen; the rotation speed was 1600 rpm; and the scan rate was 10 mV / s. -1 The 50,000-cycle durability test conditions are as follows: Square wave testing is performed at 0.6V and 0.95V vs. RHE (the reference electrode is a reversible hydrogen electrode). The voltage is held for 3 seconds at each test voltage, and one test cycle is completed in 6 seconds. This is repeated for 10,000, 30,000, and 50,000 cycles to test polarization performance, up to a maximum of 50,000 cycles. The test is conducted in a constant temperature water bath at 25℃.
[0031] Single-cell fabrication: Accurately weigh 160 mg of the catalyst prepared above; measure 16 mL of pure water, 16 mL of isopropanol, and 1.6 mL of perfluorosulfonic acid resin solution, add them to the catalyst, and disperse them thoroughly for 0.5-1 h to form a stable catalyst ink. Coat the ink evenly onto the cut proton exchange membrane, designating it as the cathode. Similarly, weigh 100 mg of platinum-carbon catalyst (TKK10EA50E), with the same proportions of the anode catalyst ink as the cathode, and coat it onto the other side of the membrane, designating it as the anode, forming the membrane electrode assembly (MEA). The gas diffusion layer uses Freudenberg H24XC483 GDL. Disassemble the balticFuelCells QCF25 quick-assembly test fixture, and sequentially place the thickness limit sheet, the first GDL, the CCM, and the second GDL. After securing them, rotate the pneumatic button to complete the clamping. After connecting the gas pipeline, perform an airtightness test. Once the airtightness is satisfactory, conduct a single-cell test.
[0032] Single-cell performance test conditions: Single cell area 25cm² 2 The stoichiometric ratio of anode to cathode is 1.5:2.0, the dew point of anode and cathode is 64℃, the anode feed pressure is 1.7 bar, the cathode feed pressure is 1.5 bar, and the battery test temperature is 80℃.
[0033] Single-cell durability test conditions: Square wave test, single-cell temperature 80℃, anode gas hydrogen, cathode gas nitrogen; anode gas flow rate 300 NCCM, cathode gas flow rate 300 NCCM; relative humidity 100%RH; anode / cathode inlet pressure: atmospheric pressure / atmospheric pressure; scan voltage 0.6V maintained for 3s, 0.95V maintained for 3s. It is recommended to perform polarization curve testing after 10,000, 30,000, and 50,000 cycles respectively.
[0034] Example 2 A method for preparing a highly durable iridium nitrogen-doped platinum cobalt carbon catalyst. The difference between this embodiment and Example 1 is that the platinum source used in step (1) is platinum sulfate tetrahydrate, the temperature is raised to 50°C, and the first nitrogen source used is melamine; the second nitrogen source used in step (2) is o-phenanthroline, and other conditions and proportions are the same as in Example 1.
[0035] The electrochemical testing conditions, single cell fabrication, single cell performance testing conditions, and durability testing conditions were the same as in Example 1.
[0036] Example 3 A method for preparing a highly durable iridium-nitrogen-doped platinum-cobalt-carbon catalyst includes the following steps: (1) Disperse 66.4g of chloroplatinic acid hexahydrate, 20g of cobalt nitrate hexahydrate and 23g of mesoporous carbon support (MH-18) in 5000g of water, and disperse them thoroughly at room temperature to form a uniform slurry. Heat the mixture to 45℃, add 38.6g of p-phenylenediamine, stir thoroughly for 5min, add sodium hydroxide solution with a concentration of 0.1mol / L to adjust the pH of the slurry to 10, and stir for 24h to form a platinum cobalt nitrogen carbon precursor slurry; (2) Add 2.05g hexachloroiridium hydrate, 10g cobalt nitrate hexahydrate, 17.1g glutamine and 4.5g mesoporous carbon support (MH-18) to 50g water and disperse them into a slurry. Add the slurry to the platinum cobalt nitrogen carbon precursor slurry in step (1), heat to 80℃ and react for 48h. Collect the precipitate after reaction, wash the precipitate repeatedly with deionized water, and vacuum dry at 80℃ for 12h to obtain iridium nitrogen doped platinum cobalt carbon precursor. (3) The iridium nitrogen-doped platinum cobalt carbon precursor obtained in step (2) was heated to 200°C and held at 10°C / min in an Ar atmosphere with a flow rate of 2000 mL / min for 30 min, then heated to 600°C and held at 4 h, then heated to 950°C and held at 2 h, and then cooled naturally to room temperature to obtain a black powder. (4) The black powder obtained after calcination in step (3) is placed in a sulfuric acid solution with a concentration of 0.5 mol / L, stirred at 30°C for 48 h to remove surface impurities, washed with deionized water until neutral, and vacuum dried at 80°C for 12 h to finally obtain the iridium nitrogen-doped platinum cobalt carbon catalyst.
[0037] The electrochemical testing conditions, single cell fabrication, single cell performance testing conditions, and durability testing conditions were the same as in Example 1.
[0038] Example 4 A method for preparing a highly durable iridium-nitrogen-doped platinum-cobalt-carbon catalyst differs from Example 3 in that the carbon support used in step (1) is acetylene black, the iridium source used in step (2) is iridium trichloride trihydrate, the second nitrogen source used in step (2) is o-phenanthroline, the heating rate in step (3) is 5°C / min, and the concentration of the acidic solution in step (4) is 1 mol / L. Other conditions and proportions are the same as in Example 3.
[0039] The electrochemical testing conditions, single cell fabrication, single cell performance testing conditions, and durability testing conditions were the same as in Example 1.
[0040] Comparative Example 1 A method for preparing an undoped platinum-cobalt-carbon catalyst includes the following steps: (1) Disperse 66.4g of chloroplatinic acid hexahydrate, 20g of cobalt nitrate hexahydrate and 23g of acetylene black in 5000g of water, and disperse them thoroughly at room temperature to form a uniform slurry. Heat the mixture to 45℃, add 38.6g of p-phenylenediamine, stir thoroughly for 5min, add sodium hydroxide solution with a concentration of 0.1mol / L to adjust the pH of the slurry to 10, and stir the reaction for 24h to form a platinum cobalt carbon precursor slurry; (2) The platinum cobalt carbon precursor slurry obtained in step (1) was heated to 200℃ and held at 10℃ / min under an Ar atmosphere with a flow rate of 2000 mL / min. The temperature was then increased to 600℃ and held at 600℃ for 4 hours. The temperature was then increased to 950℃ and held at 950℃ for 2 hours. The mixture was then cooled to room temperature to obtain a black powder. (3) The black powder obtained after calcination in step (2) was stirred at 30°C for 48 hours with a sulfuric acid solution of 0.5 mol / L to remove surface impurities. It was washed with deionized water until neutral and then vacuum dried at 80°C for 12 hours to finally obtain undoped platinum cobalt carbon catalyst.
[0041] The electrochemical testing conditions, single cell fabrication, single cell performance testing conditions, and durability testing conditions were the same as in Example 3.
[0042] from Figure 1 As can be seen from the high-resolution transmission electron microscope image of the iridium nitrogen-doped platinum cobalt carbon catalyst alloy particles in Example 2, the particle lattice structure is clear, indicating that the particles have good crystallinity, relatively uniform spacing between particles, and good dispersion. The Ir content in the catalyst is 0.5 wt%.
[0043] from Figure 2It can be seen that the characteristic diffraction peaks (111), (200), and (220) of platinum-cobalt in Example 3 and Comparative Example 1 are all shifted to the right, indicating that a platinum-cobalt carbon catalyst structure was prepared after the reaction. In Example 3, the iridium doping amount was 1.5 wt%, and the characteristic peak shift was smaller and the particle size was smaller after doping, which improved the dispersibility, indicating that iridium nitrogen doping has an impact on the catalyst structure.
[0044] from Figure 3 It can be seen that in the three-electrode system, after 50,000 durability cycles, the mass activity of the catalyst decreases very little, only 2.37%. This indicates that the mass activity of the iridium-nitrogen-doped platinum-cobalt-carbon catalyst hardly decreases after 50,000 durability cycles, which is conducive to the rapid advancement of the industrial application of fuel cells.
[0045] A single fuel cell fabricated using the alloy catalyst prepared according to the method of Example 3 of this invention underwent a 50,000-cycle square wave durability test. Single-cell durability test conditions: Square wave test, single-cell temperature 80℃, anode gas hydrogen, cathode gas nitrogen; anode gas flow rate 300 NCCM (Normal Cubic Centimeters per Minute), cathode gas flow rate 300 NCCM; relative humidity 100%RH; anode / cathode inlet pressure: atmospheric pressure / atmospheric pressure; scan voltage 0.6V maintained for 3s, 0.95V maintained for 3s. It is recommended to perform polarization curve testing after 10,000, 30,000, and 50,000 cycles. Single-cell performance test conditions: single-cell area 25cm². 2 The stoichiometric ratio of anode to cathode is 1.5:2.0, the dew point of anode and cathode is 64℃, the anode feed pressure is 1.6 bar, the cathode feed pressure is 1.5 bar, and the battery test temperature is 80℃.
[0046] 0.8A / cm 2 The durability of a catalyst can be largely demonstrated at a given current density. From Figure 4 It can be concluded that the iridium nitrogen-doped platinum cobalt carbon catalyst prepared in Example 3 has a performance of 0.8 A / cm 2 At that current density, the voltage drop before and after durability testing is 13mV. And from... Figure 5 It can be concluded that the single cell prepared in Comparative Example 1 without platinum-cobalt-carbon catalyst, after 50,000 square wave durability cycles, maintains a speed of 0.8 A / cm². 2The voltage drop was 51 mV. The durability decay voltage of the catalyst prepared in Example 3 was significantly reduced. It is speculated that the catalyst prepared by the method of the present invention, on the one hand, disperses trace amounts of iridium in a specific form and forms an Ir–N structure with the nitrogen source, providing high-density, high-binding-energy anchoring sites for the platinum-cobalt alloy, which significantly inhibits particle migration and agglomeration during high-temperature heat treatment or long-term operation; on the other hand, iridium and nitrogen synergistically regulate the electronic structure of the platinum-cobalt alloy surface, reduce the tendency of Co oxidation and dissolution, and inhibit structural deformation. The doping of trace amounts of iridium and nitrogen significantly extends the life of the membrane electrode.
[0047] Finally, it should be noted that the above specific embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A method for preparing a highly durable iridium-nitrogen-doped platinum-cobalt-carbon catalyst, characterized in that, Includes the following steps: (1) Disperse the platinum source, cobalt nitrate hexahydrate and carbon support in water, and fully disperse them at room temperature to form a uniform slurry. Heat the slurry to 40-50℃, add an appropriate amount of the first nitrogen source, stir thoroughly, adjust the pH of the slurry to 9.5-10.5, and stir for 1-24 hours to form a platinum-cobalt-nitrogen-carbon precursor slurry. (2) Add iridium source, cobalt nitrate hexahydrate, second nitrogen source and carbon support to an appropriate amount of water and disperse them into a slurry. Add the slurry to the platinum cobalt nitrogen carbon precursor slurry in step (1), heat to 60-80℃ and react for 4-48h. Collect the slurry after reaction and precipitate. Wash the precipitate repeatedly with deionized water and vacuum dry at 60-80℃ for 4-12h to obtain iridium nitrogen doped platinum cobalt carbon precursor. (3) The iridium nitrogen-doped platinum cobalt carbon precursor obtained in step (2) is heated to 200-250°C at a heating rate of 5-10°C / min under a calcination atmosphere and held for 20-40 min. Then, the temperature is increased to 600-700°C and held for 2-8 h. Finally, the temperature is increased to 800-950°C and held for 1-2 h. The mixture is then naturally cooled to room temperature to obtain a black powder. (4) The black powder obtained in step (3) is placed in an acidic solution and stirred at 30-50°C for 2-48 hours to remove surface impurities. It is then washed with deionized water until neutral and dried under vacuum at 60-80°C to finally obtain an iridium nitrogen-doped platinum cobalt carbon catalyst. In step (1), the first nitrogen source is one or more of melamine, ethylenediamine, and p-phenylenediamine; In step (2), the second nitrogen source is one or more of dimethylimidazole, o-phenanthroline and glutamine.
2. The method for preparing the highly durable iridium-nitrogen-doped platinum-cobalt-carbon catalyst according to claim 1, characterized in that, In step (1), the platinum source is one of chloroplatinic acid hexahydrate and platinum sulfate tetrahydrate; In steps (1) and (2), the carbon support is one or more of mesoporous carbon support and acetylene black.
3. The method for preparing the highly durable iridium-nitrogen-doped platinum-cobalt-carbon catalyst according to claim 1, characterized in that, In step (1), the platinum source is chloroplatinic acid hexahydrate, the carbon support is a mesoporous carbon support, and the first nitrogen source is p-phenylenediamine or ethylenediamine.
4. The method for preparing the highly durable iridium-nitrogen-doped platinum-cobalt-carbon catalyst according to claim 1, characterized in that, In step (2), the iridium source is one or more of hexachloroiridate hydrate, ammonium hexachloroiridate, and iridium trichloride trihydrate.
5. The method for preparing the highly durable iridium-nitrogen-doped platinum-cobalt-carbon catalyst according to claim 1, characterized in that, In step (3), the roasting atmosphere is one or more of nitrogen, argon and hydrogen.
6. The method for preparing the highly durable iridium-nitrogen-doped platinum-cobalt-carbon catalyst according to claim 1, characterized in that, In step (4), the acidic solution is one or a mixture of several of hydrochloric acid, sulfuric acid, acetic acid and citric acid, with a concentration of 0.5-1 mol / L.
7. The method for preparing the highly durable iridium-nitrogen-doped platinum-cobalt-carbon catalyst according to claim 1, characterized in that, In step (4), the iridium-nitrogen-doped platinum-cobalt-carbon catalyst contains 0.5-1.5% iridium, 0.5-2% nitrogen, 40-50% platinum, 3-5% cobalt, and the remainder is carbon.
8. A highly durable iridium-nitrogen-doped platinum-cobalt-carbon catalyst, characterized in that, It is prepared by the preparation method described in any one of claims 1-7.
9. The application of the highly durable iridium-nitrogen-doped platinum-cobalt-carbon catalyst as described in claim 8, characterized in that, The catalyst is used in fuel cells, specifically as the fuel cell cathode.
Citation Information
Patent Citations
High-performance Pt-based three-alloy catalyst and preparation method thereof
CN110635146A
Nitrogen-Functionalized Platinum-Iridium Electrocatalyst
US20180131008A1